Associations between WNT signaling pathway-related gene polymorphisms and risks of osteoporosis development in Chinese postmenopausal women: a case–control study. (4th May 2022) - Yang, Z.; Liu, J.; Fu, J.; Li, S.; Chai, Z.; Sun, Y.
Abstract: Background: The WNT signaling pathway is involved in the regulation of bone homeostasis, and the effect of WNT signaling pathway-related gene ( WNT16 and LRP5 ) polymorphisms on osteoporosis risk among Chinese postmenopausal women is still unknown. Hence, we performed a case–control study to assess the association of WNT signaling pathway-related gene polymorphisms and osteoporosis risk. Methods: A total of 1026 women (515 osteoporosis patients and 511 controls) of postmenopausal age who were randomly sampled from Xi'an 630 Hospital (Shaanxi Province, China) were involved in this study. Seven genetic polymorphisms in WNT16 (rs3779381, rs3801387, rs917727 and rs7776725) and LRP5 (rs2291467, rs11228240 and rs12272917) were selected and genotyped using the Agena MassARRAY iPLEX system. The association of the genetic polymorphisms and osteoporosis risk was assessed by odds ratios and 95% confidence intervals. The multifactor dimensionality reduction (MDR) method was conducted to analyze single nucleotide polymorphism (SNP)–SNP interaction. Results: We found that LRP5 polymorphisms (rs2291467, rs11228240 and rs12272917) were significantly associated with a decreased risk of osteoporosis in homozygote, recessive and additive models ( p  < 0.05). Stratification analysis showed that LRP5 polymorphisms (rs2291467, rs11228240 and rs12272917) significantly decreased the osteoporosis risk in the subgroup of body mass index (BMI) ≤ 24 ( p  < 0.05) and that individuals carrying a heterozygote genotype of WNT16 polymorphisms (rs3779381, rs3801387, rs917727 and rs7776725) had a higher osteoporosis risk in the subgroup of BMI > 24 ( p  < 0.05). Two haplotypes (haplotype 1: rs3779381, rs3801387, rs917727 and rs7776725; haplotype 2: rs2291467 and rs11228240) were observed, yet only Trs2291467 Trs11228240 and Crs2291467 Crs11228240 had a strong association with a decreased risk of osteoporosis ( p  < 0.05). Additionally, MDR analysis revealed that LRP5 rs2291467 was the best model in single-locus MDR analysis. A seven-locus model including rs3779381-AG, rs7776725-TC, rs3801387-GA and rs917727-TC in WNT16 and rs11228240-CC, rs12272917-TC and rs2291467-CC in LRP5 was the best model in multiple-loci MDR analysis ( p  < 0.001). These two best models were the most significantly associated with osteoporosis risk. Conclusions: Our findings suggested that WNT16 and LRP5 genetic polymorphisms are associated with osteoporosis risk among Chinese postmenopausal women.